Il GIS nei temi di cooperazione internazionale: il fenomeno del land grabbing - Caiaffa, Emanuela; Cavallini, Annalisa (GEOmedia, 2014)
The land grabbing phenomenon, which is distinguished and characterized by its spatial nature, has invested vast areas of the world and in particular the African continent. With the suppo rt of GIS , the socioeconomic conditions of these territories are classified, characterized and reported in cartographic representations having the advantage of assessing the phenomenon where physically and territorially happ ens. The land grabbing phenomenon continues inexorably to steal land to disadvantaged pop ulations that typically inhabit rural soc ieties: the aim of this article, and in particular of the case study on Mozambique, it's to show a way to monitor the phenomenon, and, although in a descriptive way, to identify areas with greater vulnerability.